All Yersinia Are Not Created Equal: Phenotypic Adaptation to Distinct Niches Within Mammalian Tissues - Davis, Kimberly M. (Frontiers in Cellular and Infection Microbiology, 2018)
Yersinia pseudotuberculosis replicates within mammalian tissues to form clustered bacterial replication centers, called microcolonies. A subset of bacterial cells within microcolonies interact directly with host immune cells, and other subsets of bacteria only interact with other bacteria. This establishes a system where subsets of Yersinia have distinct gene expression profiles, which are driven by their unique microenvironments and cellular interactions. When this leads to alterations in virulence gene expression, small subsets of bacteria can play a critical role in supporting the replication of the bacterial population, and can drive the overall disease outcome. Based on the pathology of infections with each of the three Yersinia species that are pathogenic to humans, it is likely that this specialization of bacterial subsets occurs during all Yersiniae infections. This review will describe the pathology that occurs during infection with each of the three human pathogenic Yersinia, in terms of the structure of bacterial replication centers and the specific immune cell subsets that bacteria interact with, and will also describe the outcome these interactions have or may have on bacterial gene expression.